DNA methylation biomarker candidates for early detection of colon cancer - Yi, Joo Mi (2012)
Promoter CpG island hypermethylation of tumor suppressor genes is a common hallmark of all human cancers. Many researchers have been looking for potential epigenetic therapeutic targets in cancer using gene expression profiling with DNA microarray approaches. Our recent genome-wide platform of CpG island hypermethylation and gene expression in colorectal cancer (CRC) cell lines revealed that FBN2 and TCERG1L gene silencing is associated with DNA hypermethylation of a CpG island in the promoter region. In this study, promoter DNA hypermethylation of FBN2 and TCERG1L in CRC occurs as an early and cancer-specific event in colorectal cancer. Both genes showed high frequency of methylation in colon cancer cell lines (>80% for both of genes), adenomas (77% for FBN2, 90% for TCERG1L, n=39), and carcinomas (86% for FBN2, 99% for TCERG1L, n=124). Bisulfite sequencing confirmed cancer-specific methylation of FBN2 and TCERG1L of promoters in colon cancer cell line and cancers but not in normal colon. Methylation of FBN2 and TCERG1L is accompanied by downregulation in cell lines and in primary tumors as described in the Oncomine™ website. Together, our results suggest that gene silencing of FBN2 and TCERG1L is associated with promoter DNA hypermethylation in CRC tumors and may be excellent biomarkers for the early detection of CRC.